Quasimonotone Systems of Higher Order - Kronz, Manfred (Bollettino della Unione Matematica Italiana B, 2003)
We consider higher order quasimonotone nonlinear systems of divergence type with growth of order p, p ≥ 2, and Dini continuous coefficients. Using the technique of harmonic approximation we give a direct partial regularity proof for weak solutions.
UnivIS-Import:2015-03-09:Pub.2003.nat.dma.lma2.quasim